Automated detection of estrous behavior in tie-stall housing using a barometer and accelerometer - Hisashi NABENISHI; Shunsei KAWAKAMI; Shota SHIMO; Kaito TAKESHITA; Atusi YAMAZAKI; Kazuhiro SUZUKI (The Society for Reproduction and Development, 2018)
Tie-stall housing inhibits movement in cows, thereby restricting the behavioral indicators used by farmers for detecting estrous. In this study, we investigated the changes in patterns of lying and standing times at estrous, and evaluated the potential for automated detection of estrous within tie-stalls using a barometer and accelerometer. On estrous days, total daily standing time was significantly longer than that during non-estrous days (P < 0.05). A practical method was developed for detecting slight altitude changes using a novel device, which consisted of a barometer and accelerometer, and was attached to the neckband. Total daily standing time predicted using this new device was found to be highly correlative with the observed measured data (r = 0.95, P < 0.01), indicating the accuracy of the device in measuring daily standing time in tie-stall housed cows. In addition, the device detected an overall increase in total daily standing time during estrous days.